Vitrification freezing of large ovarian tissue in the human body - Qian Zhao; Ying Zhang; Ke Su; Xiao-Wan Wang; Pan-Pan Hai; Bing Han; Ai-Ping Bian; Rui-Xia Guo (BMC, 2019)
Abstract Background This study aims to carry out the vitrification freezing of a large ovarian tissue in the human body, and evaluate its feasibility. Results A total of 18 ovarian tissues in the human body were selected, and each tissue was cut into three large ovarian cortex slices. These tissues were randomly divided into three groups: vitrification freezing group (group A), programmed freezing group (group B), and fresh control group (group C). Then, the morphological analysis and apoptosis detection of each ovarian tissue was carried out, followed by the recycling of ovarian tissues at three weeks after the heterotransplantation of nude mice, in order to detect the follicle preservation conditions. The immunohistochemistory method was applied to detect the follicle activity. In comparing the proportion of primordial follicle with normal morphology after unfreezing between group A and group B, the difference was not statistically significant (P > 0.05). Furthermore, the incidence of follicle apoptosis in group A and group B was higher than that in the group C (P < 0.05). However, when comparing between group A and group B, the difference was not statistically significant (P > 0.05). The interstitial cell apoptosis rate in group A was lower than that of the group B, showing that the difference was statistically significant (P < 0.05). Conclusions Compared with programmed freezing, the vitrification freezing of large ovarian tissues in the human body was feasible to a certain extent. This can be used as an alternative scheme to realize the freeze preservation of ovarian tissues in the human body.